Predictors of adverse pregnancy outcomes among postnatal women in a secondary hospital in Eastern Kenya - Menge, Daniel; Kikuvi, Gideon; Wanyoike, Salome (International Journal Of Community Medicine And Public Health, 2025)
Background: Adverse pregnancy outcomes remain a major public health concern in eastern Kenya, contributing to maternal and neonatal morbidity and mortality. These outcomes are influenced by socio-demographic, economic, intrapartum, and neonatal factors. This study examined their predictors at a County Referral Hospital in eastern Kenya to guide targeted interventions. Methods: An analytical cross-sectional design combining quantitative and qualitative methods was used among a sample of 210 postnatal women selected through systematic sampling. Data from medical records, focus group discussions, and key informant interviews was collected. Quantitative data were analyzed using descriptive statistics, chi-square tests, logistic regression, and qualitative data was thematically analysed. Results: Adverse outcomes occurred in 19.9% of participants, with stillbirth and neonatal asphyxia each accounting for 5.5%. Unmarried women had significantly higher rates (31.7% versus 15.1%, p=0.007). Prolonged third-stage labour (p=0.013), preterm delivery (p=0.008), abnormal birth weight (p<0.001), and low Apgar scores at 1, 5, and 10 minutes (p<0.001) were strongly associated. Logistic regression showed that longer first (p=0.050, AOR=1.002) and third (p=0.038, AOR=1.128) stages of labour increased the likelihood of adverse outcomes. Conclusions: Stillbirth and neonatal asphyxia were the most frequent complications. Strengthening intrapartum care, ensuring timely management of prolonged labour, improving monitoring of preterm and low-birth-weight infants, and enhancing support for unmarried mothers are key to reducing adverse pregnancy outcomes.